PENGARUH PEMBERIAN TEPUNG BAWANG PUTIH (Allium sativum L) TERHADAP PERFORMANS PRODUKSI AYAM PEDAGING - Estepanus L.S. Tumbal (JURNAL HUTAN PULAU-PULAU KECIL, 2017)
This study aims to determine the effect of addition garlic powder (Allium sativum L) on broiler production performance. This study was conducted for 4 weeks using Completely Randomized Design with 4 treatments, and each treatment was repeated 3 times, with the number of chickens per unit trial of 3 chicken. The treatments were various levels of garlic powder (commercial) dissolved in drinking water, P0 (without garlic powder), P1 (with 0.5% white flour or 5 gr / liter), P2 (with garlic powder 1.0% or 10 gr / liter), and P3 (with garlic powder 1.5% or 15 gr / liter). Treatment begins at the time of chicken age 1 week until age 4 weeks, with the interval time of 2 days. Variable observed included dietary intake, weight gain, and the conversion of ransum. The results showed that giving garlic powder did not give a significantly effect (P> 0,05) to production performance either to ransum consumption, body weight gain and ransum conversion. The numerical consumption of ransum, and ransum conversion decreased with increasing of garlic starch level, while the highest chicken body weight increased in P1 treated group and the lowest in P3 treated group.